Ocean and Atmospheric Observations at the Remote Ieodo Ocean Research Station in the Northern East China Sea - Byun, Do-Seong; Jeong, Jin-Yong; Kim, Duk-jin; Hong, Sungmin; Lee, Kyu-Tae; Lee, Kitack (Frontiers in Marine Science, 2021)
For open ocean environments it is rare to find continuous, simultaneous air and sea observation records, due to the challenges of instrument installation and maintenance. The Ieodo Ocean Research Station (Ieodo ORS), a remote ocean site located in the northern East China Sea with its harsh oceanic and atmospheric environment, provides a platform for concurrent monitoring of air and sea environments. Since 2014, the Korea Hydrographic and Oceanographic Agency has run the ‘Ieodo ORS fieldtrip program’, via which researchers are able to stay at the station for a week or more. This work reports technical lessons learned over 5 years from 5 Ieodo ORS research projects launched in 2016. Over the course of these projects Ieodo ORS has monitored sea surface temperatures, temperature and salinity in the water column, seawater pH, air pollutants and solar radiation. The purpose of this paper is to facilitate the success of future research activities in similar environments by sharing our experiences and ‘best practices’.